Comparison of the intrageneric neutralization scope of monospecific, bispecific/ monogeneric and polyspecific/monogeneric antisera raised in horses immunized with subSaharan African snake venoms - Sánchez Brenes, Andrés (2024)
Background Snakebite envenomation inflicts a high burden of mortality and morbidity in sub-Saharan Africa. Antivenoms are the mainstay in the therapy of envenomation, and there is an urgent need to develop antivenoms of broad neutralizing efficacy for this region. The venoms used as immunogens to manufacture snake antivenoms are normally selected considering their medical importance and availability. Additionally, their ability to induce antibody responses with high neutralizing capability should be considered, an issue that involves the immunization scheme and the animal species being immunized. Methodology/Principal findings Using the lethality neutralization assay in mice, we compared the intrageneric neutralization scope of antisera generated by immunization of horses with monospecific, bispecific/monogeneric, and polyspecific/monogeneric immunogens formulated with venoms of Bitis spp., Echis spp., Dendroaspis spp., spitting Naja spp. or non-spitting Naja spp. It was found that the antisera raised by all the immunogens were able to neutralize the homologous venoms and, with a single exception, the heterologous congeneric venoms (considering spitting and non-spitting Naja separately). In general, the polyspecific antisera of Bitis spp, Echis spp, and Dendroaspis spp gave the best neutralization profile against venoms of these genera. For spitting Naja venoms, there were no significant differences in the neutralizing ability between monospecific, bispecific and polyspecific antisera. A similar result was obtained in the case of non-spitting Naja venoms, except that polyspecific antiserum was more effective against the venoms of N. melanoleuca and N. nivea as compared to the monospecific antiserum. Conclusions/Significance The use of polyspecific immunogens is the best alternative to produce monogeneric antivenoms with wide neutralizing coverage against venoms of sub-Saharan African snakes of the Bitis, Echis, Naja (non-spitting) and Dendroaspis genera. On the other hand, a monospecific immunogen composed of venom of Naja nigricollis is suitable to produce a monogeneric antivenom with wide neutralizing coverage against venoms of spitting Naja spp. These findings can be used in the design of antivenoms of wide neutralizing scope for sub-Saharan Africa.